2020
DOI: 10.3390/fermentation6020044
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Microbiological and Functional Properties of Camelina Meal Fermented in Solid-State Using Food Grade Aspergillus Fungi

Abstract: Camelina meal (CAM) was fermented in solid-state using food grade Aspergillus fungi (A. sojae, A. ficuum and their co-cultures), and the physicochemical composition, microbiological and functional properties were investigated. SSF increased the starch contents but reduced (p < 0.05) the contents of soluble carbohydrate. The microbiological counts of the fermented meals were higher (p < 0.05) than that of the unfermented CAM. Phytic acid content reduced (p < 0.05) in the fermented meals. SSF reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
5
11
0
Order By: Relevance
“…However, the moisture and starch of FBM were remarkably decreased (P < 0.05) in S. fibuligera or L. plantarum-fermented groups, in comparison with the control group. The results were similar with previous researches (Kaczmarska et al, 2017;Olukomaiya et al, 2020b), which showed same trend of starch and soluble carbohydrates contents in camellia meal fermented with Aspergillus sojae and A. ficuum. The decrease of starch is probably due to the fact that starch enzymes secreted by S. fibuligera and L. plantarum during the fermentation make starch decompose and convert it into carbohydrates.…”
Section: Effect Of Ssf On Proximate Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the moisture and starch of FBM were remarkably decreased (P < 0.05) in S. fibuligera or L. plantarum-fermented groups, in comparison with the control group. The results were similar with previous researches (Kaczmarska et al, 2017;Olukomaiya et al, 2020b), which showed same trend of starch and soluble carbohydrates contents in camellia meal fermented with Aspergillus sojae and A. ficuum. The decrease of starch is probably due to the fact that starch enzymes secreted by S. fibuligera and L. plantarum during the fermentation make starch decompose and convert it into carbohydrates.…”
Section: Effect Of Ssf On Proximate Compositionsupporting
confidence: 91%
“…Similarly, according to Olukomaiya et al . (2020b), the TTA content of canola meal increased significantly after single‐ or co‐SSF with A. sojae and A. ficuum . The possible reason may be attributed to the fact that carbohydrate was transformed into sugars and organic acids during fermentation (Oluseyi & Temitayo, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…At present, cold-pressed oils are the most popular vegetable fats consumed in Poland because of their health-promoting activities [1]. Camelina sativa L., (also known as "false flax") is one of the oldest crops from the Brassicaceae family (used for oil production for 3000 years [1,[7][8][9]. It receives attention for its oil, rich in beneficial ω-3 (linolenic acid) and ω-6 (linoleic acid) fatty acids [1,3,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among fungi, Rhizopus is one of the most interesting fungal genus for SSF, due to its simple nutritional requirements and growing conditions [12] and the high variety of enzymes that it can produce [13]. In addition, SSF is described as a simple treatment for digestibility improvement [14,15]. It has been successfully applied for ruminal digestibility improvement in fiber rich by-products, like corn stovers [16][17][18], wheat straw [19], camelia seed [20] and corn straw [21], among others.…”
Section: Introductionmentioning
confidence: 99%